Learning Needs Analysis for Developing AI-Powered Interactive Media in Islamic Cultural History Learning at Primary Madrasah - Kurnia Tri Puspita Ms.; Abd Muhith; Saihan (Program Studi PGMI, 2026)
This study aims to identify learning needs for developing Artificial Intelligence (AI)-powered interactive learning media in Islamic Cultural History (SKI) learning at a primary madrasah. This research employed a qualitative case study approach conducted at Madrasah Ibtidaiyah Darul Ulum Pondok Wuluh, Probolinggo. The participants consisted of 20 sixth-grade students, one SKI teacher, and one madrasah head, selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation. The findings reveal that SKI learning is predominantly conducted through conventional lecture-based methods, resulting in low student engagement. Most students (approximately 80%) expressed a preference for visual, interactive, and game-based learning media, while also reporting feelings of boredom when learning relied solely on textbooks and verbal explanations. The teacher and school leader demonstrated a positive attitude toward integrating digital technology, although limitations in technological skills and infrastructure were identified. The needs analysis indicates that AI-powered learning media should incorporate adaptive feedback, dynamic visualization, interactive features, and integration of Islamic moral values to support both cognitive and affective learning. These findings imply that the development of AI-based interactive media should be designed not only to align with students’ learning preferences but also to support teachers’ instructional practices and maintain the moral orientation of Islamic education.